Analysis of Enterprise Strategic Management Issues and Coping Strategies Based on Big Data Analysis - ZHONG Ziqi; Haoran Wang; JUNSHENG WANG (E3S Web of Conferences, 2020)
Corporate strategic management is an important management mode that affects the development of an enterprise. It plays a very important role in the development of corporate strategic management. In recent years, information technology has developed rapidly, data is frequently updated, and huge amounts of data are generated every day. Social development has entered the era of big data, which makes enterprises face more opportunities and challenges in formulating strategies and operating management. In order to enable enterprises to adapt to the development of the times and obtain healthy and sound development results. This article analyzes and summarizes the new characteristics of enterprise management in the context of big data, and applies big data analysis technology to the environmental analysis of enterprises, and points out the problems of strategic management of enterprises in the context of big data. This article aims at the current problems and proposes specific strategies after in-depth research, which provides a reference basis for strategic management of enterprises in the era of big data. It has certain practical significance and can help Chinese enterprises quickly adapt to the new environment.